Strategi Humas Dalam Mengelola Aplikasi Sibadra Untuk Keterbukaan Informasi Publik - Alvionita Anggraeni, Armastasya; Sjoraida, Diah Fatma; Hanny Hafiar (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
The public has the right to obtain public information related to the Government, so the Bogor City Diskominfo created the SiBadra application as a communication and information service facility, but in the process experienced technical problems with the system which resulted in negative complaints, for which a complaint handling strategy was created. The aim of this research is to determine the public relations strategy of the Bogor City Diskominfo in managing the SiBadra application for public information disclosure. This research uses a qualitative method with a case study approach. The data collection techniques used were observation, interviews and documentation. From the results of this research, it is known that at the defining public relations problem stage, specific research was not carried out before formulating strategic planning, but only by knowing the high number of smartphone users in the city of Bogor. The planning and programming stage was created in conjunction with the Bogor City Regional Medium Term Development Plan or RPJMD for 2019-2024. Action and communication stage by carrying out various socialization and collaboration with other OPDs. The evaluation stage of the program is carried out openly by publishing detailed weekly data recapitulation reports to the public. So that through the public relations strategy process the objectives of managing the SiBadra application can be achieved.